Mechanisms and mitigating factors for venous thromboembolism in chronic kidney disease: the REGARDS study. (9th August 2018) - Cheung, K. L.; Zakai, N. A.; Callas, P. W.; Howard, G.; Mahmoodi, B. K.; Peralta, C. A.; Judd, S. E.; Kurella Tamura, M.; Cushman, M.
Abstract : Essentials Chronic kidney disease (CKD) is associated with procoagulant and inflammatory biomarkers. We studied the association of CKD and venous thromboembolism (VTE) in a case‐cohort study. Factor VIII, D‐dimer and C‐reactive protein appeared to explain the association of CKD and VTE. Statin use was protective against VTE in those with and without CKD. Summary: Background: Chronic kidney disease (CKD) is associated with venous thromboembolism (VTE) risk via unknown mechanisms. Whether factors associated with reduced VTE risk in the general population might also be associated with reduced VTE risk in CKD patients is unknown. Objectives: To determine whether thrombosis biomarkers attenuate VTE risk, and whether factors associated with reduced VTE risk are similarly effective in CKD patients. Methods: Baseline biomarkers were measured in a cohort (294 VTE cases; 939 non‐cases) from the Reasons for Geographic and Racial Differences in Stroke (REGARDS) study, a nationwide prospective cohort study of 30 239 persons aged ≥45 years with 4.3 years of follow‐up. The hazard ratio (HR) of VTE per 10 mL min −1 1.73 m −2 decrease in estimated glomerular filtration rate (eGFR), and the percentage attenuation of this HR by each biomarker, were calculated. Associations of protective factors (physical activity, lower body mass index [BMI], and aspirin, warfarin and statin use) with VTE were estimated in those with and without CKD. Results: The HR for VTE with lower eGFR was 1.13 (95% confidence interval [CI] 1.02–1.25), and VTE risk was attenuated by 23% (95% CI 5–100) by D‐dimer, by 100% (95% CI 50–100) by factor VIII, and by 15% (95% CI 2–84) by C‐reactive protein. Normal BMI was associated with lower VTE risk in those without CKD (HR 0.47, 95% CI 0.32–0.70), but not in those with CKD (HR 1.07, 95% CI 0.51–2.22). Statin use, physical activity and warfarin use were associated with lower VTE risk in both groups. Conclusions: Procoagulant and inflammatory biomarkers mediated the association of eGFR with VTE. Higher physical activity, statin use and warfarin use mitigated VTE risk in those with CKD and those without CKD, but normal BMI did not mitigate VTE risk in CKD patients.